‘The Call of the King’ and Its Political Implications in Africa (Hekima Review, 2008)
Spirituality is not merely meant to bring about interior transformation; it also ha socio-political implications. This article fleshes out the political implications of the Ignatius meditation on the “call of the Eternal King,” taking the Democratic Republic of the Congo as a Case Study.